2017
DOI: 10.1002/dvdy.24546
|View full text |Cite
|
Sign up to set email alerts
|

Specification of neurotransmitter identity by Tal1 in thalamic nuclei

Abstract: Our results demonstrate that Tal1 plays an essential role in regulating neurotransmitter phenotype in the developing thalamic nuclei. Developmental Dynamics 246:749-758, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
(86 reference statements)
3
3
0
Order By: Relevance
“…8H). As expected based on previous studies (Lee et al, 2017a;Sellers et al, 2014;Song et al, 2015;Virolainen et al, 2012), most cells fell along the bifurcation from progenitors into rostral thalamic and prethalamic fates with sequential gene expression changes corresponding to the progression of lineage development (Fig. 8H).…”
Section: Determination Of Gene Expression Landscapes Along Developmensupporting
confidence: 88%
See 2 more Smart Citations
“…8H). As expected based on previous studies (Lee et al, 2017a;Sellers et al, 2014;Song et al, 2015;Virolainen et al, 2012), most cells fell along the bifurcation from progenitors into rostral thalamic and prethalamic fates with sequential gene expression changes corresponding to the progression of lineage development (Fig. 8H).…”
Section: Determination Of Gene Expression Landscapes Along Developmensupporting
confidence: 88%
“…This is in agreement with the notion that these two regions may share a common pool of progenitors but give rise to different subtypes of GABAergic neurons (Kataoka and Shimogori, 2008). Indeed, GABAergic precursors that arise from the rostral thalamus or pretectum retain latent plasticity for subtype identity upon cell cycle exit; removal of various transcription factors, such as Gata2, Helt and Ascl1, Tal2, and Dlx1/2 results in cell fate switching between rostral thalamus and prethalamus (Delogu et al, 2012;Lee et al, 2017a;Sellers et al, 2014;Song et al, 2015;Virolainen et al, 2012). Furthermore, the predicted close relationship between the epithalamus and the thalamus is also in line with the fact that they both arise from the p2 domain (Puelles and Rubenstein, 2003;Rubenstein et al, 1994).…”
Section: Inference Of Developmental Trajectories Of Lineage Specificasupporting
confidence: 87%
See 1 more Smart Citation
“…As development proceeds, GABA/Nkx2.2 cells are found in the Ar2, the GdN, and the IGL, similarly to the situation described in mice, where both GABA and Nkx2.2 were expressed in the ventral lateral geniculate nucleus (vLG) and in the external medullary lamina IGL (Vue et al, ), suggesting that in Xenopus at least a subpopulation of the GdN and IGL is originated in the intermediate stratum and then migrates radially to the final adult positions in the superficial stratum. Supporting this idea is the fact that in Xenopus both markers are very scarce in superficial derivatives such as the La, in contrast to the abundance noted in the Ar and Ac, (derivatives of the intermediate stratum) and that most NPY cells, specifically located in the IGL of most amniotes studied (Botchkina & Morin, ; Güntürkün & Karten, ; Kenigfest et al, ; Lee et al, ; Pinato, Frazao, Cruz‐Rizzolo, Cavalcante, & Nogueira, ) express also Nkx2.2. The nucleus of the zona limitans (described in Milán & Puelles, ) seemed to be also a pure rostral derivative in Xenopus , since it expresses exclusively rostral markers such as Nkx2.2 and GABA.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, Ascl1 and Helt act cooperatively to regulate Gata2 in GABAergic thalamic neurons. Recently, we demonstrated that Tal1 is not required for regional patterning in the caudal diencephalon, but essential for regulating post‐mitotic GABAergic neurotransmitter identity in the rTH and IGL/vLG . By contrast, loss‐ and/or gain‐of‐function analyses revealed the roles for Neurog1/2 and Pax6 in promoting glutamatergic lineage fate in the cTH .…”
Section: Introductionmentioning
confidence: 97%